RESPONSE OF SOME TOMATO CULTIVARS AGAINST ROOT-KNOT NEMATODE, Meloidogyne incognita (KOFOID & WHITE) CHITWOOD - S. Khanzada; M. M. Jiskani; S. R. Khanzada; M. S. Khanzada; S. Ali; K.A. Khanzada; N. Saeed; S. Anwar; M. Khalid (Journal of Animal and Plant Sciences, 2012)
Meloidogyne incognita (Kofoid & White) Chitwood was isolated as most predominant root-knot nematode from soil and the infected root samples of stunted tomato plants showed chlorosis. Root and shoot growth of five tomato verities was significantly reduced when inoculated with second stage infective larvae of M. incognita as compared to un-inoculated tomato varieties. M. incognita significantly reduced root length in tomato variety Anmol followed by Gola France and Sunehra as compared to un-inoculated tomato variety Roma Holland and Roma v.f. Root weight was also decreased in Sunehra followed by Roma Holland and Tomato Anmol than that of un-inoculated tomato variety Roma v.f., followed by Roma Holland. Shoot length was significantly increased in tomato variety Sunehra followed by Roma v.f. and Roma Holland and that was decreased in tomato Anmol as compared to un-inoculated tomato variety Roma Holland, Sunehra and Roma v.f. respectively. Shoot weight was significantly reduced in tomato variety Anmol inoculated with M. incognita as compared to Gola France, Roma v.f., and Sunehra than that of un-inoculated tomato varieties Roma v.f., Roma Holland and Anmol, respectively. The development of root galls and eggs formation were increased in all tomato varieties inoculated with M. incognita. Population of larvae and egg-laying females were also greater in all inoculated tomato varieties.  Variation in multiplication of nematode in certain tomato was observed among varieties. The number of root-galls was significantly increased in tomato variety Roma v.f. followed by Roma Holland as compared to Gola France and Sunehra and that was decreased in tomato variety Anmol. The greater number of egg masses per root system was obtained in tomato variety Roma v.f. followed by Roma Holland and Gola France and minimum was recorded in Tomato Anmol, respectively. Maximum number of eggs per egg mass was found in tomato variety Roma v.f. followed by Roma Holland and Gola France as compared to Sunehra and Tomato Anmol. Number of larvae was significantly increased in tomato variety Roma v.f., Gola France followed by Roma Holland and that was decreased in Anmol. Population of egg-laying females of M. incognita was also increased in tomato variety Roma v.f. followed by Gola France and Roma Holland than that of tomato variety Sunehra and Tomato Anmol, respectively. However, the tomato varieties usually cultivated in Sindh are highly susceptible to root-knot nematode and thus provide substrate to build up the population of root-knot nematode in tomato field. These varieties should be replaced in order to reduce the population of root-knot nematode. The use of resistant varieties to manage the population of nematode is very cheep and an effective control of plant parasitic nematode but it require time and facilities to develop resistant varieties
Keywords: Root-Knot; Nematode; Tomato and Meloidogyne incognita (Kofoid & White) Chitwood.